TO TEACH LANGUAGE LIKE THE ESSENCE, SPIRIT AND ACTIVITY OF A PERSON - Masudjon kizi, Muminova Mohinur (Miasto Przyszłości, 2023)
An improvement in the expression of human identity the process of using language, this speech, he also discovered such ways of combining his pieces with each other that as a result he became the author of a miraculous tool called artistic speech. Words created as unique forms and examples of such beautiful speech are form on the basic of phonetic sounds.